Seeking Scientific Consensus - An Expert Survey on the Replication Debate between Acemoglu et al. (2001) and Albouy (2012) - Martin Buchner; Julian Rose; Magnus Johannesson; Mandy Malan; Jörg Ankel-Peters (Institute for Replication (I4R), 2025)
Consensus is crucial to authoritative science, as is replicability. Yet, in economics and the social sciences, the publication of contradictory replications often sparks fierce debates between replicators and original authors. This paper investigates whether experts can reach a consensus on a famous yet unsettled debate about the robustness of the seminal paper by Acemoglu, Johnson, and Robinson (AJR, 2001) following a replication by Albouy (2012). We recruited 352 experts mainly from the pool of scholars citing one of the involved or similar articles. Through a structured online questionnaire, we assess the extent to which these experts align with AJR or Albouy. Our findings indicate no consensus on whether the original results hold after Albouy's replication, although there is a slight tendency among experts to side with the replicator. Exploratory heterogeneity analysis suggests that experts with greater academic credentials are more likely to align with Albouy. Our study demonstrates a potential way to scope scientific consensus formation and navigate replication debates and contested literatures.
https://osf.io/fx8p5/
Keywords: 330; replication; scientific consensus; scientific credibility; expert survey; institutions and growth